2017
DOI: 10.1080/09637486.2017.1350941
|View full text |Cite
|
Sign up to set email alerts
|

Higher adherence to the Mediterranean diet is inversely associated with having hypertension: is low salt intake a mediating factor?

Abstract: Blood pressure (BP) is a major risk factor for population health worldwide and a preventable disease through lifestyle modification. The aim of this study was to assess the association between adherence to the Mediterranean diet (MD) and occurrence of hypertension in a Mediterranean cohort. Demographic and dietary data of 1937 adults were collected in 2014-2015 from the general population of Catania, Sicily (Italy). Food frequency questionnaires and a MD adherence score were used to assess exposure variables. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
37
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 68 publications
4
37
1
Order By: Relevance
“…The findings of this study are partially consistent with observed trends in scientific literature, showing a slow abandonment of healthy dietary habits among individuals living in southern Italy, leading to adverse metabolic-related health conditions [22][23][24]. Adherence to traditional healthy dietary patterns has been associated to lower risk of metabolic disorders and cardiovascular outcomes among individuals living in southern Italy [25][26][27], including hypertension [28], obesity [29], dyslipidemia [30], insulin resistance [31] but also overall quality of life [32]. Nevertheless, there is evidence of the so-called "nutrition transition" phenomenon, described as a shift toward Westernized dietary habits, including high-sugar, high-refined, high-fat processed foods and beverages in spite of more natural, biologic (or less processed), local goods [33,34]; these trends have been demonstrated especially among younger generations [ [35][36][37].…”
Section: Discussionsupporting
confidence: 89%
“…The findings of this study are partially consistent with observed trends in scientific literature, showing a slow abandonment of healthy dietary habits among individuals living in southern Italy, leading to adverse metabolic-related health conditions [22][23][24]. Adherence to traditional healthy dietary patterns has been associated to lower risk of metabolic disorders and cardiovascular outcomes among individuals living in southern Italy [25][26][27], including hypertension [28], obesity [29], dyslipidemia [30], insulin resistance [31] but also overall quality of life [32]. Nevertheless, there is evidence of the so-called "nutrition transition" phenomenon, described as a shift toward Westernized dietary habits, including high-sugar, high-refined, high-fat processed foods and beverages in spite of more natural, biologic (or less processed), local goods [33,34]; these trends have been demonstrated especially among younger generations [ [35][36][37].…”
Section: Discussionsupporting
confidence: 89%
“…The Mediterranean dietary pattern has been associated with lower risk of cardio-metabolic disorders [ 56 , 57 , 58 , 59 , 60 , 61 ]. Previous results from this cohort showed a significant inverse association between higher adherence to this dietary pattern and hypertension [ 62 ]; however, another study showed that phenolic acid intake was associated in a non-linear manner to high adherence to the Mediterranean diet, suggesting that certain food sources of such polyphenol group not included in the classical paradigm of key features of the Mediterranean diet may provide beneficial action toward cardiovascular health [ 63 ]. Additionally, other studies conducted on a similar population (a sample recruited in the same southern Italian area) reported that food groups not included in the Mediterranean diet (i.e., coffee and beer) were associated with better metabolic health [ 64 , 65 , 66 ].…”
Section: Discussionmentioning
confidence: 78%
“…High salt is a risk factor for hypertension [ 20 , 21 ]. To establish the animal model of hypertension, we fed rats with a high salt diet (8% NaCl enriched diet) for 9 weeks.…”
Section: Resultsmentioning
confidence: 99%
“…Sodium is an essential nutrient and the primary cation in the extracellular fluid [ 22 , 23 ]. Previous study has shown that rats with high salt diet has higher sodium levels in the interstitial space [ 21 ]. To check the effect of high salt intake on intracellular calcium concentration, we used calcium-sensitive indicator Fluo-3 AM to measure intracellular calcium concentration [Ca 2+ ] i by fluorescence.…”
Section: Resultsmentioning
confidence: 99%